2016
DOI: 10.1063/1.4960732
|View full text |Cite
|
Sign up to set email alerts
|

Resonance energy transfer: The unified theory via vector spherical harmonics

Abstract: A general formula for the rate of resonant transfer of energy between two electric multipole moments of arbitrary order using molecular quantum electrodynamics J. Chem. Phys. In this work, we derive the well-established expression for the quantum amplitude associated with the resonance energy transfer (RET) process between a pair of molecules that are beyond wavefunction overlap. The novelty of this work is that the field of the mediating photon is described in terms of a spherical wave rather than a plane wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In 2016, Grinter and Jones re-derived expression (7) using a spherical wave description of the mediating photon, via vector spherical harmonics [66]. All previous derivations employed a plane-wave description of the mediating photon.…”
Section: Ret Coupling Tensor: the Quest For Its Correct Formmentioning
confidence: 99%
“…In 2016, Grinter and Jones re-derived expression (7) using a spherical wave description of the mediating photon, via vector spherical harmonics [66]. All previous derivations employed a plane-wave description of the mediating photon.…”
Section: Ret Coupling Tensor: the Quest For Its Correct Formmentioning
confidence: 99%
“…In the region between the emitter and the absorber the out-going field generated by the emitter interacts with the in-coming field of the absorber, also expressed by Eq. 3, but with a Hankel function of second kind [25,26]. In adherence to the principle of timereversal invariance, when both fields are expressed in a single coordinate system, their interaction, and hence the probability of photon transfer, is proportional to the Hermitian scalar product of the two fields, E JlM…”
mentioning
confidence: 99%
“…The long-standing semiclassical treatment encapsulated in the well-known Förster theory is based on a nonretarded description of electromagnetic fields [141], which was shown to strictly fail to conform to the demands of causality [142,143]. By correctly describing the interaction between the transition moments of the donor and acceptor in terms of virtual photon propagation, it emerges from QED analysis that the short-and long-range mechanisms previously considered radiationless and radiative, respectively, are simply two asymptotic limits of a unified theory of energy transfer, fully accommodating both retardation and quantum uncertainty effects [123,124,[144][145][146][147][148]. Inter alia, the QED analysis also showed that the two supposedly different mechanisms can never compete in determining the distance-dependent dynamics of energy transfer.…”
Section: A Differences In Perspectivementioning
confidence: 99%